Universal and Specific Predictors of Chinese Children With Dyslexia – Exploring the Cognitive Deficits and Subtypes - Song, Shuang; Zhang, Yuping; Shu, Hua; Su, Mengmeng; McBride, Catherine (Frontiers in Psychology, 2020)
While previous studies have shown that the impact of phonological awareness (PA) and rapid automatized naming (RAN) on dyslexia depends on orthographic complexity in alphabetic languages, it remains unclear whether this relationship generalizes to the more complex orthography of Chinese. We investigated the predictive power of PA, RAN, and morphological awareness (MA) in dyslexia diagnosis status in a sample of 241 typically developing and 223 dyslexic Chinese-speaking children. Compared with the control group, children with dyslexia performed notably worse on character reading and all three cognitive measures. A logistic regression analysis showed that PA and RAN were both significant predictors, while MA also played a relatively important role for predicting dyslexia status in Chinese children. In the next step, we used multigroup analyses to test if these three cognitive predictors were of the same importance in predicting reading variance in different reading proficiency groups. And the results showed that the regression coefficient of MP is stronger for the control group than the dyslexia group, while the regression coefficient of PD tends to be stronger for the dyslexic group. Further cluster analysis identified four subtypes of dyslexia in this sample: a global deficit group, a phonological deficit group, a RAN deficit group, and a mild morphological deficit group. Our findings are largely consistent with previous studies of predictors of dyslexia, while uniquely demonstrating the differences in predictive power of these three cognitive variables on reading, as well as the unique contribution of MA in Chinese reading.